(untitled) (International Journal of Current Engineering and Technology, 2014)
For high rise structures depending upon the precision required and limit state considered an engineer shall perform response analysis with suitable idealization for loading and geometry of the structure. The structural response for wind loads can be made more realistic by assuming wind loads as harmonic instead of quasi static approaches of equivalent static loads. Any sustained cyclic load produces a harmonic response in the building. When the natural frequency of a multi-storey building matches the frequency of forcing excitations resonance occurs causing maximum displacement. In the present context, Harmonic response technique is then adopted on ANSYS platform for a fifteen storey structure bare frame and employing mode superposition method displacements of the structure at various floor levels are evaluated. Peak displacement is then visualized from the frequency v/s displacement graph obtained from mode superposition of reduced modes at forcing frequencies.